Analisis Toolpath Melingkar Terhadap Objek Acrylic Pada Cnc Miling Rakitan - Oktaviano, Oddi, Bambang Waluyo Febriantoko, ST., MT, Ir. Ngafwan, MT (2016)
Purpose of the research on tool path of the home-made CNC machine is to know cutting speed of two different paths resulted from feeding in working on a work piece or product. Next stage of the process of making CNC machine was preparation of materials and instruments used in the research process. Then, design of the machine was made and specified parts of the machine construction used aluminum and iron materials. After the machine was completed, setting of application and calibration was conducted. The machine was tested to work on a product and data was collected from the testing. The data was analyzed. Results of The machining test of CNC milling with phased feeding in making a product showed that the greatest speed of cutting was found at feeding speed of 300mm/min, namely 118.868 m/min. Meanwhile, test of spiral feeding indicated the greatest cutting speed was found at feeding speed of 300 mm/min, namely 69.238 m/min. Thus, it can be concluded that the greater feeding speed, the greater cutting speed, and it was known that the phased feeding produced greater speed of cutting than spiral feeding.